Military intelligence in Cyprus - Dimitrakis, Panagiotis. (London)
xiv, 223 sayfa, [16] sayfa resim
Keywords: “Since World War I, Cyprus has played a crucial role in British defence strategy. Panagiotis Dimitrakis here introduces new research which reveals the true role of British intelligence on the island throughout the twentieth century, particularly during World War II, the 1955-59 Archbishop Makarios and EOKA-led revolt and the 1974 Turkish invasion. He sheds fresh light on the stance of both Prime Minister Harold Wilson and Foreign Secretary James Callaghan towards Greece and Turkey in the turbulent 1970s, and provides important new perspectives on the 1978 Egyptian hostage crisis at Larnaca Airport and the research is based throughout on primary sources including previously unpublished declassified papers from British diplomats and intelligence officers. This is a valuable study for scholars of contemporary strategy and military history and for those interested in military intelligence and the history of Cyprus“ --